WHICH SECTORS DRIVE EGYPT’S GROWTH AND EMPLOYMENT? - Mohmed Kamal , Azza (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2018)
According to the International Monetary Fund, Egypt’s employment elasticity of growth in the last two decades was relatively low, as previous policies focused on capital deepening rather than improving labor utilization growth rate. This paper uses input-output analysis to identify the economic activities that have high output and employment multipliers at the subsector level of manufacturing and services in Egypt, while previous multiplier research for Egypt analyzed manufacturing as an aggregate sector. The top 20 ranking subsectors in terms for employment multipliers include 13 services and 7 manufacturing subsectors. Except for food and accommodation services, most of the services subsectors gain their high rank from direct and induced employment, with little contribution of backward interlinkages. The picture is mixed for manufacturing. For example, most of the employment eﬀect of food products and beverages is attributed to the interlinkage with the agriculture sector, but the direct and induced employment eﬀects are small. The paper presents an illustrative exercise which excludes imported intermediate inputs in order to account for the possible overestimation of the multiplier eﬀect due to imports. The employment multiplier is reduced by more than 30% in the sectors which use intermediate inputs from high import upstream sectors.